Population dynamics of reef fish in the Kwandang Bay, Sulawesi Sea, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Achmad DS, Gani S, Ardiansyah W, Mokoginta MM, Nurdin MS, Jompa J, Indrianti MA, Achmad N. 2022. Population dynamics of reef fish in the Kwandang Bay, Sulawesi Sea, Indonesia. Biodiversitas 23: 5217-5226. The grouper stocks in Kwandang Bay, Sulawesi Sea, Indonesia, are dominated by orange-spotted grouper (Epinephelus coioides) and coral trout (Plectropomus leopardus). However, the Kwandang Bay grouper fishery is currently experiencing serious challenges due to population decline resulting in a decline in both the average size of fish caught and the production volume. This study was conducted in Kwandang Bay, Sulawesi Sea, from January to December 2021. The population dynamics parameters estimated were growth, recruitment, mortality, exploitation rate and yield per recruit. The results showed that the total length (TL) of E. coioides and P. leopardus ranged from 16.50-101 cm and 17.90-60 cm, respectively, with Von Bertalanffy K-coefficients of 0.38 and 0.69, respectively. Recruitment occurred during most of the year, with respective recruitment value ranges of 0.99-17.11% and 0.08-19.22%. Natural and fishing mortality was 0.69/year-1 and 0.87/year-1 for E. coioides, 1.16/year-1 and 1.47/year-1 for P. leopardus. Beverton and Holt yield per recruit analysis indicated recruitment overfishing of both E. coioides and P. leopardus. Fishing regulations are needed to maintain a sustainable grouper fishery, including a 25% reduction in fishing vessels and gear, to enable the groupers of Kwandang Bay to spawn at least once during their life cycle.
Keywords: Grouper, recruitment overfishing, stock